Evolution and synthesis of novel orally bioavailable inhibitors of PDE10A. Issue 9 (1st May 2015) - Burdi, Douglas F.; Campbell, John E.; Wang, Jun; Zhao, Sufang; Zhong, Hua; Wei, Jianfeng; Campbell, Una; Shao, Liming; Herman, Lee; Koch, Patrick; Jones, Philip G.; Hewitt, Michael C.
Graphical abstract The evolution and synthesis of potent, orally bioavailable inhibitors of PDE10A is described.